2014
DOI: 10.1371/journal.pone.0107615
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy, Computer Skills and Quality of Patient-Physician Communication in Chinese Patients with Cataract

Abstract: PurposeThe aim of the study was to assess levels of health literacy and computer skills in Chinese patients with cataract, and their impact on the doctor-patient relationship.MethodsWe undertook a cross-sectional study of cataract patients scheduled for cataract extraction procedures in Guangdong Province, China. Generic health literacy was assessed using 3 established screening questions. Adequate computer skills was determined if patients had used a computer and routinely used search engines on the Internet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Previous studies also suggested that improving patients’ perceived level of understanding was an important factor to maximize patient satisfaction with cataract surgery[11, 12]. Patients with adequate health literacy presumably had a full understanding of potential benefits and risks of cataract surgery[17]. It is therefore not surprising that adequate health literacy was a significantly positive predictor of the discrepancy between actual and expected postoperative improvement of VF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies also suggested that improving patients’ perceived level of understanding was an important factor to maximize patient satisfaction with cataract surgery[11, 12]. Patients with adequate health literacy presumably had a full understanding of potential benefits and risks of cataract surgery[17]. It is therefore not surprising that adequate health literacy was a significantly positive predictor of the discrepancy between actual and expected postoperative improvement of VF.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown in an earlier study, that Chinese elderly patients with cataract had inadequate health literacy and computer skills, which were significantly associated with poor patient-physician communication and increase the risk of patient misunderstanding and mismanaging the ocular conditions[17]. Previous studies also suggested that improving patients’ perceived level of understanding was an important factor to maximize patient satisfaction with cataract surgery[11, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline questionnaire takes about 30 minutes to complete and will not be compensated. The baseline questionnaire will be sent to women in all groups to collect sociodemographic, health and computer literacy, 29 menopause knowledge and attitude, SDM, and MHV use data. Follow-up questionnaires for the intervention and comparison participants will be collected at 6-months.…”
Section: Data Collectionmentioning
confidence: 99%
“…Across studies, evidence suggests that patient characteristics, such as anxiety (Guo, 2014; Lucas, Cox, Perry, & Bridges, 2013; Pereira, Figueiredo‐Braga, & Carvalho, 2016), health literacy (De Oliveira, McCarthy, Wolf, & Holl, 2015; Lin et al, 2014; Ortiz, Wang, Elayda, & Tolpin, 2015), surgical risk (Govender, Spurrett, & Biccard, 2015; Grocott, 2010; Levett, Edwards, Grocott, & Mythen, 2016), and type of surgery (Burkle et al, 2014; Ortiz et al, 2015), influence patient readiness, which in turn can influence surgical outcomes. Related surgical outcomes with a patient focus include perception of pain, postoperative analgesic consumption (Ali et al, 2014; Angioli et al, 2014; Wilson et al, 2015), patient experience or satisfaction (Greene et al, 2017; Guo, 2014), and complications (Ali et al, 2014; De Oliveira et al, 2015; Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%